Pengaruh E-Service Quality dan Experiential Marketing terhadap Repurchase Intention dengan Trust sebagai Variabel Intervening (Studi pada Konsumen Aplikasi Agoda di Denpasar): - - Julyastini , Ni Kadek Dwita; Maharani, Ni Putu Devighita Tasya; Suryantari, Ida Ayu Putu; Giantari, I Gst. Ayu Kt.; Ekawati , Ni Wayan (Universitas Warmadewa, 2023)
The purpose of this research is to develop marketing strategies that are suitable for online travel agent applications in order to increase the number of repurchase intentions on the AGODA application. This study used non-probability sampling, with 100 total samples. The analysis technique used is Path Analysis. In order to increase Repurchase intention, the Agoda application must take specific actions based on the implications of this research result. This involves focusing on the customer experience, building trust, maintaining long-term relationships, monitoring and improving the quality of electronic services, and strengthening their communications and reputation. The results of this study show that E-Service Quality influences Trust in a significant positive way. E-service quality and Experiential marketing influence Trust in a significant positive way. E-Service Quality and Experience Marketing influence Repurchase intention in a significant positive way. Based on the results of the statistical test, it can be concluded that indirectly E-Service Quality and Experience marketing through Trust have a significant positive effect on Repurchase Intention.